PRODUKSI INULINASE DAN KECEPATAN PERTUMBUHAN SPESIFIK ISOLAT KHAMIR DUCC Y-015 PADA BERBAGAI KONSENTRASI TEPUNG UMBI DAHLIA - Dani Ika Purwaningsih; Arina Tri Lunggani; Endang Kusdiyantini (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
Inulin is an abundant compound in the nature after starch. Hydrolytic enzyme called inulinase is able to catalyse hydrolysis reaction of inulin polysaccharides into fructose and fructooligosaccharide (FOS). Yeast isolateDUCC Y-015 is one of the microbes that is able to produceinulinase. The action of inulinase enzyme associated with the growth of the isolate. Specific growth rate is one of the measurement of growth parameters; itis defined as the increase in cell biomass per unit time in the growth phase of the microbes. This study aims to examine theinulinase production and specific growth rate of yeast isolate DUCC Y-015 on the medium with various concentrations of dahlia tuber flour. The measurement of growth was done by weighing the cell dry weight and inulinase activity test was done by calculating the reduction sugar using DNS method. The used concentrations of dahlia tuber flourin the medium were 2%, 3%, 4% and 5%. Inulinase activity in each treatment was 0,111 IU/ml, 0,147 IU/ml, 0,113 IU/ml and 0,119 IU/ml, respectively, whereas the specific growth rate was 0,0062 hour-1, 0,0081 hour-1, 0,0077 hour-1, 0,0052 hour-1, respectively. The resultswere tested using the Mann-Whitney Test and theKruskal-Wallis Test. According to the results, the most optimuminulinase production and specific growth rate (µ) of yeast isolate DUCC Y-015 on dahlia tuber flour medium was treated with 3% concentration of dahlia tuber flour.Keywords: Dahlia Tuber Flour, Yeast Isolate DUCC Y-015, Specific Growth Rate, Inulinase Activity